Information Literacy As An Implementation Of Tabayun Concept In Islam - Muhamad Riza (Institut Agama Islam Negeri (IAIN) Curup, 2021)
The concept of Information Literacy (IL) may be recognized as a recent concept. Along with the growth of information technology, other literacy such as Digital Literacy emerged as consequences of unfamiliarity with the new-emerging technology. However, Information Literacy is as relevant as the technology itself particularly todays. In an era in which users are flooded with information, and most of information they receive are frequently irrelevant to what they need. In addition, with the abundance of information available on the internet, most of the time the information they get are invalid. The example of fake news circulating on social media as we may have heard many times is because people are not able to evaluate information they receive. This paper explores the way in which the concept of Information Literacy is related to and found on the concept of Tabayun in Islam. The carefulness of evaluating information as the prophet Muhammad used to do when he received information that possibly be disinformation is one of the scopes in Information Literacy. The paper use library research method in discribing the key concepts of Information Literacy and Tabayyun of Information in Islam.the findings of the paper explores ways in which information can be evaluated through saveral methods and theories in order to get better, valid and reliable information